Flow Shop Scheduling Problem in Neutrosophic Environment Using Trapezoidal Fuzzy Numbers - Santhi , S. (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we propose to solve the flow shop scheduling problem using Branch and Bound method. This paper presents an algorithm with the help of branch and bound approach for a flow shop scheduling problems consisting of 4 jobs and 4 machines in which the processing time as Neutrosophic trapezoidal fuzzy numbers which are further converted in to crisp value using graded mean ranking method. Numerical example is given to illustrate the study of solvingflow shop scheduling under Neutrosophic trapezoidal fuzzy number using branch and bound technique.